An azithromycin electrochemical sensor based on an aniline MIP film electropolymerized on a gold nano urchins/graphene oxide modified glassy carbon electrode - Jafari, Saied; Dehghani, Mohammad; Nasirizadeh, Navid; Azimzadeh, Mostafa (Journal of electroanalytical chemistry (Lausanne, Switzerland), 2018)
In this study, a selective and sensitive procedure was developed based on a molecular imprinted polymer to detect and determine Azithromycin (AZT) antibiotic. AZT-aniline MIP films were electropolymerized (to form polyaniline) on the surface of gold nanourchin/graphene oxide modified glassy carbon electrodes (GNU/GO/GCE), with aniline serving as a monomer and AZT as a template. The morphological and analytical properties of the fabricated nanosensor were characterized by field emission scanning electron microscopy, cyclic voltammetry and electrochemical impedance spectroscopy. The selectivity, linear range, limit of detection, sensitivity and repeatability of the proposed procedure were also evaluated. The analytical performance of the presented sensor that was assessed through differential pulse voltammetry proved to be in the linear range of 0.3 nM to 920.0 nM with the detection of limit 0.1 nM for AZT. In addition, the average current and precision in terms of the relative standard deviation for eight repetitive measurements in 60.0 nM AZT were found to be 0.293 ± 0.07 μA and 2.5% respectively. The proposed sensor was successfully applied for the detection of AZT in human serum. [Display omitted] •A novel nanosensor based on GNU/GO/MIP has been developed for determination of AZT.•GNU/GO/MIP improves electron transfer, analytical signal, and sensitivity of the GCE to AZT.•The linear range was 0.3 nM to 920.0 nM with the detection of limit 0.1 nM for AZT.•The nanosensor showed high selectivity and good function in real sample without significant function defect.